(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study found problems in the sample to be studied, where the problem was in the athlete’s acceleration, which was lacking when doing the push and the overall push time of the athletes was still in the lacking category if included in the test norm. For that, the researcher created a press-up and pull-up training program to solve the problems studied. This study aims to determine the effect of press-up and pull-up exercises on arm muscle power in female shot put athletes of the Dumpang Athletics Club (KDA) in 2025. The study used a quantitative approach with an experimental method, specifically a two-group pre-test post-test design. This study involved 6 athletes selected through a purposive sampling technique. Data collection was carried out through a Medicine ball test during the pre-test and post-test. Data analysis used a paired sample t-test with the help of SPSS version 22. The results of the analysis showed that press-up and pull-up exercises had a statistically significant effect on increasing arm muscle power. This is shown by the comparison of the average value of the medicine ball test before and after treatment, namely the average pre-test of 2.05 with a standard deviation of 0.74, and the average post-test of 2.74 with a standard deviation of 0.72. After being tested statistically, it was found to provide a significant increase. Thus, it can be concluded that press-up and pull-up exercises have a significant effect on increasing arm muscle power in female shot put athletes of the Dumpang Athletics Club (KDA) in 2025.